Buoyant Density of the Hepatitis A Virus-Like Particle in Cesium Chloride - Feinstone, S. M. (1974)
We recently visualized by immune electron microscopy a virus-like particle in the stools of patients with hepatitis A. The particle measured approximately 27 nm in diameter and morphologically resembled a picornavirus or parvovirus. To further characterize this particle, we have determined its buoyant density in cesium chloride (CsCl) by ultracentrifugation. Hepatitis A particles from three positive stool specimens were isopycnically banded in separate experiments, and the gradient fractions were examined for particles by immune electron microscopy by using hepatitis A convalescent sera. In each experiment, the particles were observed in a normal distribution about a peak fraction with a mean density of approximately 1.4 g/cm(3). The buoyant density of 1.4 g/cm(3) in CsCl together with its morphology and the reported resistance of hepatitis virus to acid, ether, and heat suggest that this particle is parvovirus-like.